Prenatal Diagnosis of Sirenomelia - Aykut Özek; Mert Turğal; Özgür Özyüncü; Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine)
Sirenomelia is a rare and lethal congenital malformation. It is associated with a variety of anomalies and oligo/anhydramniosis. We present a case of sirenomelia detected in early second trimester presenting with anhydramniosis.